1990
DOI: 10.1038/bjc.1990.279
|View full text |Cite
|
Sign up to set email alerts
|

Anal cancer and marital status

Abstract: Summary Anal cancer is a rare tumour in Britain and its epidemiology has not previously been studied in this country. Several studies from the United States have shown an association between single marital status at the time of tumour registration (as a marker of male homosexuality in these populations) and the incidence of anal cancer. This study has used registry information on martial status for anal cancer The registrations for anal and colonic cancers were tabulated, by gender, marital status (single, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…These early reports have been supported by data from Dalinget al [23] and Scholefield et al [24], Daling et al [23] interviewed 148 persons with anal cancer and a further 166 control patients who had had colon cancer between 1978 and 1985. They found that in men with a history of receptive anal intercourse there was a strong correlation with occurrence of anal cancer with a relative risk of 33.1 (95% confidence interval, 4.0 to 272.1).…”
Section: Homosexualitysupporting
confidence: 67%
See 1 more Smart Citation
“…These early reports have been supported by data from Dalinget al [23] and Scholefield et al [24], Daling et al [23] interviewed 148 persons with anal cancer and a further 166 control patients who had had colon cancer between 1978 and 1985. They found that in men with a history of receptive anal intercourse there was a strong correlation with occurrence of anal cancer with a relative risk of 33.1 (95% confidence interval, 4.0 to 272.1).…”
Section: Homosexualitysupporting
confidence: 67%
“…[24] assessed anal cancer registrations with respect to gender, marital status and 5-year age group in three regional cancer registries from England and Scotland. They found that the relative risk of develop ing anal cancer was significantly increased in single men in all three registries [24],…”
Section: Homosexualitymentioning
confidence: 99%
“…It may be that the effect of HPV infection is less in penis cancer than in the other cancers, as recently suggested (Tornesello et al, 2008). Several studies have linked sexual behaviour with cancer of the anus (Daling et al, 1987;Scholefield et al, 1990;Frisch et al, 1993Frisch et al, , 1997. In both Denmark (Melbye and Biggar, 1992) and Scotland (Brewster and Bhatti, 2006) a higher prevalence of receptive anal intercourse in women than in men has been reported, and may explain in part the higher incidence of anal cancer in women in these countries.…”
Section: Discussionmentioning
confidence: 79%
“…Increasing trends in anal cancer have been reported, possibly due to changes in sexual practices (Daling et al, 1987;Scholefield et al, 1990;Frisch et al, 1993Frisch et al, , 1997. If this were the case, a strong generational effect would be expected in the incidence trends of anogenital cancers.…”
mentioning
confidence: 99%
See 1 more Smart Citation